The construction of cubic Bezier curve / Siti Sarah Raseli, Nur Ain Mohd Khusairy Faisal and Norpah Mahat - Raseli, Siti Sarah; Mohd Khusairy Faisal, Nur Ain; Mahat, Norpah (Universiti Teknologi MARA, Perlis, 2022)
The construction of Bezier curves is one of the curves that are commonly discussed in Computer-Aided Geometric Design (CAGD). This study focuses on cubic Bezier curve. The objectives in this study are to review the properties of cubic Bezier curve and construct the cubic Bezier curves. In this study, the expanding equations from the basis function of the curve is used to construct the cubic Bezier curve. Future researchers can expand the degree of the Bezier curves, which is more useful in Computer-Aided Design (CAD), CAGD and engineering. The next studies in Bezier curve are recommended as a contribution for further research.